The real interest rates across monetary policy regimes - Hernán D. Seoane (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
This paper reviews the main theories of interest rate determination and studies the dynamics of the real interest rate in US. Using cointegration techniques we search for equilibrium relationships between the real interest rate, monetary factors and real factors and we study how these relationships change with the policy regimes. We analyze monthly US data since early 20th century and find equilibrium relationships between a measure of the real interest rate, the policy interest rate and industrial production growth only after the end of the Bretton Woods. Moreover, we find that the equilibrium relationships between these variables are not invariant to changes in the monetary policy regime.
Keywords: 330; Realzins; Kointegration; Geldpolitik; USA